A cross-linked hyaluronic acid-smooth hydroxyapatite gel and a method for preparing the same
Patent Information
- Application Number
- CN202311128445.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-09-04
AI Technical Summary
[0006]鉴于现有技术中羟基磷灰石人体填充剂类产品存在填充效果持续时间短,填充效果差的问题,本发明提出一种交联透明质酸-光滑羟基磷灰石凝胶及其制备方法,不但填充效果持续时间长,填充效果好,还能大批量制备,适于工业化生产
[0028] (1) The cross-linked hyaluronic acid-smooth hydroxyapatite gel of the present invention is prepared by hydrothermal method to obtain dense and smooth hydroxyapatite microspheres. The smooth surface helps to reduce the injection extrusion force of the cross-linked hyaluronic acid-smooth hydroxyapatite gel, and the dense structure makes the microsphere content higher, which is beneficial to stimulate the growth of dermal tissue. This makes the cross-linked hyaluronic acid-smooth hydroxyapatite gel of the present invention less prone to degradation in the human body fluid environment, with a long filling duration and a long time to support the growth of human filling tissue, thus providing excellent filling effect for the skin for a long time.
Smart Images

Figure CN117323471B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical technology, and in particular to a cross-linked hyaluronic acid-smooth hydroxyapatite gel and its preparation method. Background Technology
[0002] Hyaluronic acid is a biodegradable high-molecular-weight mucopolysaccharide found in the matrix of connective tissue. It possesses excellent moisturizing properties and biocompatibility. By promoting epidermal cell proliferation and differentiation, and scavenging oxygen free radicals, it can promote skin regeneration at injured sites and has a regulatory effect on human skin. It is commonly used as an ingredient in medical aesthetic products (such as whitening, moisturizing, and wrinkle-reducing products), particularly for preventing facial wrinkles and filling fat atrophy. However, conventional hyaluronic acid is prone to enzymatic degradation in the human body's fluid environment, resulting in poor in vivo stability and a short duration of effect.
[0003] Hydroxyapatite, a major component of human bone, exhibits excellent biocompatibility and is a commonly used material in bone tissue engineering. Hydroxyapatite microspheres can be used as fillers, frequently for facial filling and fat grafting. After injection, hydroxyapatite forms a scaffold for human cell growth, providing a platform for cell growth and stimulating the body to accelerate the generation of filler cells, thus creating a long-lasting filling effect.
[0004] Chinese patent CN114767934A, "A Preparation Method of Injectable Facial Filler Hydrogel for Cosmetic Surgery," discloses a method for preparing an injectable facial filler hydrogel for cosmetic surgery. The method involves preparing hydroxyapatite microspheres via spray drying. However, the hydroxyapatite microspheres prepared by this method are porous, have low density, and, due to their low content and numerous pores, degrade rapidly in the human body fluid environment, typically metabolizing completely within a few months. This results in a short duration of filling effect; the microspheres, which provide support, disappear before the human filler tissue has fully grown, leading to low growth efficiency of the human filler tissue and poor filling effect.
[0005] Therefore, it is of great significance to research and develop a hydroxyapatite human filler with a long-lasting and effective filling effect, as well as its preparation method and application. Summary of the Invention
[0006] In view of the problems of short duration and poor filling effect of existing hydroxyapatite filler products, this invention proposes a cross-linked hyaluronic acid-smooth hydroxyapatite gel and its preparation method, which not only has a long duration and good filling effect, but also can be prepared in large quantities and is suitable for industrial production.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a cross-linked hyaluronic acid-smooth hydroxyapatite gel includes the following steps:
[0009] S1. Prepare solutions A and B with concentrations of 0.1–5 mol / L. Add a morphology control agent to solution B, stir and mix, adjust the pH to 5–8, and then add solution A to the mixed solution B. Adjust the pH of the mixture to 9–14, seal and stir, let it stand to precipitate, and obtain precipitate A. Centrifuge precipitate A, ultrasonically clean it, dry it, ball mill it and sieve it to obtain calcium carbonate template microspheres.
[0010] Solution A is one or more of sodium carbonate aqueous solution, potassium carbonate aqueous solution, and ammonium carbonate aqueous solution; solution B is one or more of calcium chloride aqueous solution, calcium hydroxide aqueous solution, and calcium nitrate aqueous solution.
[0011] S2. Prepare 0.01-1 mol / L solution C, add calcium carbonate template microspheres obtained in S1, stir to form a suspension, adjust the pH of the suspension to 8-14, heat, cool naturally to room temperature, centrifuge, ultrasonically clean to obtain precipitate B, dry precipitate B, ball mill and sieve to obtain hydroxyapatite microspheres.
[0012] The C solution is one or more of the following: diammonium hydrogen phosphate aqueous solution, disodium hydrogen phosphate aqueous solution, and dipotassium hydrogen phosphate aqueous solution;
[0013] S3. Weigh out the hyaluronic acid raw material and alkaline solution according to the mass fraction, stir, add the hyaluronic acid crosslinking agent alkaline solution, add the hydroxyapatite microspheres obtained in S2, and obtain the pre-crosslinking mixture. Heat and crosslink to obtain the post-crosslinking mixture. Sieve under pressure to refine. Add phosphate buffer and acid neutralization solution to the refined post-crosslinking mixture, shake and mix to obtain the pre-dialysis mixture. Transfer the pre-dialysis mixture to a dialysis bag and dialyze in dialysis solution to obtain the post-dialysis mixture.
[0014] S4. Add the hydroxyapatite microspheres and phosphate buffer obtained in S2 to the dialysis mixture obtained in S3, stir to disperse fully, refine, vacuum fill, and steam sterilize to obtain the cross-linked hyaluronic acid-smooth hydroxyapatite gel.
[0015] Furthermore, the power of the stirring and mixing agitator described in S1 to S4 is independently 1 to 10 kilowatts, and the rotation speed is independently 300 to 3000 rpm;
[0016] The ultrasonic cleaning time in S1 and S2 is 1 to 10 minutes, and the number of times is 1 to 10. The ultrasonic cleaning also includes a centrifugation step after cleaning, and the centrifugation speed is 100 to 3000 rpm.
[0017] The ball mill sieving machines described in S1 and S2 have an independent power of 5 to 400 kilowatts and an independent speed of 500 to 2000 rpm. The sieving uses 325 mesh and 625 mesh screens respectively.
[0018] Furthermore, in S2, the ratio of the amount of calcium ions in the calcium carbonate template microspheres to the amount of phosphate ions in solution C should be 5:3; the heating temperature is 100–160°C, and the time is 6–36 hours; the ultrasonic cleaning solution is distilled water; the drying temperature is 40–80°C, and the drying time is 1–24 hours.
[0019] Furthermore, the intrinsic viscosity in S3 is 0.5–4 m³ / kg, the molecular weight is 10,000–160,000, and the mass fraction is 1–10 parts; the alkaline solution is an alkaline aqueous solution of sodium hydroxide and / or potassium hydroxide, with a mass fraction of 10–100 parts and a concentration of 0.1–10 wt.%.
[0020] The hyaluronic acid crosslinking agent in the alkaline solution is one or more of pentanediol, butylene glycol diglycidyl ether, genipin, ethylene glycol diacrylate, adipate dihydrazide, and divinyl sulfone. The mass fraction of the hyaluronic acid crosslinking agent is 0.06 to 0.6 parts, and the mass fraction of the alkaline solution is 0.2 to 2 parts.
[0021] The hydroxyapatite microspheres are present in a mass fraction of 2.5 to 25 parts.
[0022] Furthermore, the heating crosslinking temperature described in S3 is 30–70°C, and the time is 0.5–5 hours.
[0023] Furthermore, in S3, the phosphate buffer solution is in the form of 30–300 parts by mass; the acidic neutralizing solution is hydrochloric acid and / or sulfuric acid, with a concentration of 0.1–5 mol / L and a mass fraction of 2–20 parts; the shaking mixing speed is 50–100 rpm, and the time is 1–48 hours; the dialysate is phosphate buffer and / or physiological saline; the dialysis stirring speed is 100–1000 rpm, the time is 10–72 hours, and the number of times the solution is changed is 1–10.
[0024] Furthermore, in S4, the amount of hydroxyapatite microspheres added is 1.5 to 15 parts, and the amount of phosphate buffer added is 0.2 to 2 parts; the size of the refined particles is 60 to 1500 micrometers; the steam sterilization pressure is -0.1 to -1 MPa, the temperature is 100 to 150°C, and the time is 1 to 20 minutes.
[0025] Another object of the present invention is to provide the above-mentioned cross-linked hyaluronic acid-smooth hydroxyapatite gel.
[0026] A cross-linked hyaluronic acid-smooth hydroxyapatite gel is prepared according to any one of the above preparation methods.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0028] (1) The cross-linked hyaluronic acid-smooth hydroxyapatite gel of the present invention is prepared by hydrothermal method to obtain dense and smooth hydroxyapatite microspheres. The smooth surface helps to reduce the injection extrusion force of the cross-linked hyaluronic acid-smooth hydroxyapatite gel, and the dense structure makes the microsphere content higher, which is beneficial to stimulate the growth of dermal tissue. This makes the cross-linked hyaluronic acid-smooth hydroxyapatite gel of the present invention less prone to degradation in the human body fluid environment, with a long filling duration and a long time to support the growth of human filling tissue, thus providing excellent filling effect for the skin for a long time.
[0029] (2) The cross-linked hyaluronic acid-smooth hydroxyapatite gel of the present invention has mild reaction conditions and is environmentally friendly. The cross-linked hyaluronic acid-smooth hydroxyapatite gel is obtained by cross-linking hyaluronic acid and smooth hydroxyapatite, which makes it have excellent filling effect and long filling duration. It is suitable for mass production and industrial production, and is easy to use and has excellent application prospects. Attached Figure Description
[0030] The invention will be further illustrated with reference to the accompanying drawings, but the embodiments in the drawings do not constitute any limitation on the invention. For those skilled in the art, other drawings can be obtained based on the following drawings without any creative effort.
[0031] Figure 1 Scanning electron microscope image of the smooth hydroxyapatite microspheres prepared in Example 1.
[0032] Figure 2 Scanning electron microscope image of porous hydroxyapatite microspheres prepared for Comparative Example 1.
[0033] Figure 3 The image shows the XRD pattern of the smooth hydroxyapatite microspheres prepared in Example 1.
[0034] Figure 4 Scanning electron microscope image of the cross-linked hyaluronic acid-smooth hydroxyapatite gel prepared in Example 1.
[0035] Figure 5 The absorbance bar graphs for Example 1 and Comparative Example 1 of the MTS cytotoxicity experiment are shown.
[0036] Figure 6 Absorbance bar charts for MTS cytotoxicity assay Example 1 and Comparative Example 2
[0037] Figure 7 The T2-weighted axial images are for Example 1 and Comparative Example 1.
[0038] Figure 8 Images of stained tissue sections from Example 1 and Comparative Example 1. Detailed Implementation
[0039] To better illustrate the objectives, technical solutions, and advantages of this invention, the following embodiments are provided. Obviously, the following embodiments are only a part of the embodiments of this invention, and not all of them; it should be understood that the embodiments of this invention are only used to illustrate the technical effects of this invention, and not to limit the scope of protection of this invention.
[0040] All raw materials used in the examples are commercially available; unless otherwise specified, the reagents, methods and equipment used in this invention are conventional reagents, methods and equipment in this technical field.
[0041] Example 1
[0042] A method for preparing a cross-linked hyaluronic acid-smooth hydroxyapatite gel includes the following steps:
[0043] S1. Prepare 0.5 mol / L sodium carbonate aqueous solution and calcium chloride aqueous solution. Add citric acid to the calcium chloride aqueous solution to make the citric acid concentration in the mixture 0.1 mol / L. Stir and mix at 5 kW 1000 rpm. Adjust the pH to 7 with 1 mol / L sodium hydroxide solution. Add sodium carbonate aqueous solution to the mixture. Adjust the pH to 12 with sodium hydroxide solution again. Seal and stir for 60 min. Let stand and precipitate for 24 h to obtain precipitate A. Centrifuge to remove the supernatant. Add anhydrous ethanol or distilled water and ultrasonically clean for 3 min. After cleaning, centrifuge at 500 rpm to separate the cleaning solution from precipitate A. Change the cleaning solution for the next cleaning. Repeat the cleaning with each cleaning solution 3 times. Dry at 40℃ for 24 h. Ball mill at 100 kW 1000 rpm and sieve. The ground powder is sieved through 325 mesh and 625 mesh screens to obtain calcium carbonate template microspheres with an outer diameter of 25-45 micrometers and a smooth surface.
[0044] S2. Prepare a 0.06 mol / L diammonium hydrogen phosphate aqueous solution, add the calcium carbonate template microspheres obtained in S1, and add them until the ratio of calcium ions in calcium carbonate to phosphate ions in diammonium hydrogen phosphate is 5:3. Stir to form a suspension, adjust the pH of the suspension to 12 with 1 mol / L sodium hydroxide solution, and then transfer it to a reaction vessel with a polytetrafluoroethylene liner. Heat at 140℃ for 24 h, cool naturally to room temperature, pour out the internal suspension, centrifuge to remove the supernatant, add distilled water and ultrasonically clean for 3 min. After cleaning, centrifuge at 500 rpm to separate distilled water and precipitate B. Replace the distilled water for the next cleaning. Clean 3 times to obtain precipitate B, dry at 40℃ for 24 h, ball mill at 100 kW and 1000 rpm and sieve. The ground powder is then sieved through 325 mesh and 625 mesh sieves to obtain hydroxyapatite microspheres with an outer diameter of 25-45 micrometers and a smooth surface.
[0045] S3. Weigh 3.5 parts by weight, the intrinsic viscosity is 2.5m. 3 / kg of hyaluronic acid raw material and 31 parts of 1wt.% sodium hydroxide aqueous solution were added to a double planetary mixer container and stirred at 300rpm for 30min. Then, 1 part of butylene glycol diglycidyl ether sodium hydroxide aqueous solution (containing 0.25 parts of butylene glycol diglycidyl ether and 0.75 parts of 1wt.% sodium hydroxide aqueous solution) was added, followed by 8.9 parts of hydroxyapatite microspheres. The mixture before crosslinking was obtained and heated at 50℃ for 2.5h to obtain the mixture after crosslinking. The crosslinked product was transferred to a pressure sieve and pulverized to a particle size of 100 micrometers. The refined crosslinked mixture was then... 105 parts of phosphate buffer and 7.5 parts of 1 mol / L hydrochloric acid were added and placed on a shaker at 75 rpm for 12 hours to obtain the predialysis mixture. The predialysis mixture was transferred to an automatic dispensing machine with a dispensing pressure of 1 MPa. The predialysis mixture was transferred to the dialysis bag through the automatic dispensing machine, with 8.5 g of predialysis mixture per centimeter of dialysis bag. Excess air in the dialysis bag was removed and the bag was placed in a mixture of phosphate buffer and physiological saline in a stirrer for dialysis for 45 hours at a stirring speed of 300 rpm. The phosphate buffer was changed periodically during the dialysis, for a total of 4 changes. The postdialysis mixture was obtained after the dialysis was completed.
[0046] S4. The dialysis mixture obtained in S3 is placed in a dual planetary mixer container, and 4.7 parts of hydroxyapatite microspheres and 2 parts of phosphate buffer are added. The mixture is stirred at 300 rpm for 30 min to ensure thorough dispersion. The cross-linked hyaluronic acid-smooth hydroxyapatite gel is then pulverized to 100 micrometers using a pressure sieve. After degassing, the cross-linked hyaluronic acid-smooth hydroxyapatite gel is transferred to a pre-filled syringe vacuum filling and capping machine. The filling capacity is set to 1 mL, and the working gas pressure is 1 MPa. The cross-linked hyaluronic acid-smooth hydroxyapatite gel is transferred to the pre-filled syringe using the vacuum filling and capping machine. The pre-filled syringe containing the cross-linked hyaluronic acid-smooth hydroxyapatite gel is then transferred to a 600-liter large-scale pressure steam sterilizer for sterilization. The sterilization temperature is set to 121°C, the sterilization time is 6 minutes, and the sterilization pressure is 0.6 MPa, thus obtaining the cross-linked hyaluronic acid-smooth hydroxyapatite gel.
[0047] Example 2
[0048] A method for preparing a cross-linked hyaluronic acid-smooth hydroxyapatite gel includes the following steps:
[0049] S1. Prepare 1 mol / L potassium carbonate aqueous solution and calcium nitrate aqueous solution. Add citric acid to the calcium nitrate aqueous solution to make the citric acid concentration in the mixture 0.5 mol / L. Stir and mix at 5 kW 1000 rpm. Adjust the pH to 7 with 1 mol / L sodium hydroxide solution. Add potassium carbonate aqueous solution to the mixture. Adjust the pH to 12 with sodium hydroxide solution again. Seal and stir for 60 min. Let stand and precipitate for 24 h to obtain precipitate A. Centrifuge to remove supernatant. Add anhydrous ethanol or distilled water and ultrasonically clean for 3 min. After cleaning, centrifuge at 500 rpm to separate the cleaning solution from precipitate A. Change the cleaning solution for the next cleaning. Repeat the cleaning with each cleaning solution 3 times. Dry at 40℃ for 24 h. Ball mill at 100 kW 1000 rpm and sieve. The ground powder is sieved through 325 mesh and 625 mesh screens to obtain calcium carbonate template microspheres with an outer diameter of 25-45 micrometers and a smooth surface.
[0050] S2. Prepare a 0.6 mol / L disodium hydrogen phosphate aqueous solution, add the calcium carbonate template microspheres obtained in S1, and add them until the molar ratio of calcium ions in calcium carbonate to phosphate ions in disodium hydrogen phosphate is 5:3. Stir to form a suspension, adjust the pH of the suspension to 12 with 1 mol / L sodium hydroxide solution, and then transfer it to a reaction vessel with a polytetrafluoroethylene liner. Heat at 140℃ for 24 h, cool naturally to room temperature, pour out the internal suspension, centrifuge to remove the supernatant, add distilled water and ultrasonically clean for 3 min. After cleaning, centrifuge at 500 rpm to separate distilled water and precipitate B. Replace the distilled water for the next cleaning. Clean 3 times to obtain precipitate B, dry at 40℃ for 24 h, ball mill at 100 kW and 1000 rpm and sieve. The ground powder is then sieved through 325 mesh and 625 mesh sieves to obtain hydroxyapatite microspheres with an outer diameter of 25-45 micrometers and a smooth surface.
[0051] S3. Weigh 5 parts by weight, the intrinsic viscosity is 2.5m. 3 / kg of hyaluronic acid raw material and 50 parts of 1wt.% sodium hydroxide aqueous solution were added to a double planetary mixer container and stirred at 300rpm for 30min. One part of butylene glycol diglycidyl ether sodium hydroxide aqueous solution (containing 0.3 parts of butylene glycol diglycidyl ether and 1 part of 1wt.% sodium hydroxide aqueous solution) was added, followed by 11.2 parts of hydroxyapatite microspheres, to obtain the pre-crosslinking mixture. The mixture was heated at 50℃ for 2.5h for crosslinking to obtain the post-crosslinking mixture. The post-crosslinking product was transferred to a pressure sieve and pulverized to a particle size of 100 micrometers. The refined post-crosslinking mixture was then added... 115 parts of phosphate buffer and 15 parts of 1 mol / L hydrochloric acid were placed on a shaker and shaken at 75 rpm for 12 hours to obtain a predialysis mixture. The predialysis mixture was transferred to an automatic dispensing machine with a dispensing pressure of 1 MPa. The predialysis mixture was transferred into the dialysis bag through the automatic dispensing machine, with 8.5 g of predialysis mixture per centimeter of the dialysis bag. Excess air was removed from the dialysis bag, and the bag was placed in a mixture of phosphate buffer and physiological saline in a stirrer for dialysis for 45 hours at a stirring speed of 300 rpm. The phosphate buffer was changed periodically during the dialysis, for a total of 4 changes. After the dialysis was completed, the postdialysis mixture was obtained.
[0052] S4. The dialysis mixture obtained in S3 is placed in a dual planetary mixer container, and 5.3 parts of hydroxyapatite microspheres and 2 parts of phosphate buffer are added. The mixture is stirred at 300 rpm for 30 min to ensure thorough dispersion. The cross-linked hyaluronic acid-smooth hydroxyapatite gel is then pulverized to 100 micrometers using a pressure sieve. After degassing, the cross-linked hyaluronic acid-smooth hydroxyapatite gel is transferred to a pre-filled syringe vacuum filling and capping machine. The filling capacity is set to 1 mL, and the working gas pressure is 1 MPa. The cross-linked hyaluronic acid-smooth hydroxyapatite gel is transferred to the pre-filled syringe using the vacuum filling and capping machine. The pre-filled syringe containing the cross-linked hyaluronic acid-smooth hydroxyapatite gel is then transferred to a 600-liter large-scale pressure steam sterilizer for sterilization. The sterilization temperature is set to 121°C, the sterilization time is 6 minutes, and the sterilization pressure is 0.6 MPa, thus obtaining the cross-linked hyaluronic acid-smooth hydroxyapatite gel.
[0053] Example 3
[0054] A method for preparing a cross-linked hyaluronic acid-smooth hydroxyapatite gel includes the following steps:
[0055] S1. Prepare 2 mol / L ammonium carbonate aqueous solution and calcium chloride aqueous solution. Add citric acid to the calcium chloride aqueous solution to make the citric acid concentration in the mixture 0.1 mol / L. Stir and mix at 5 kW 1000 rpm. Adjust the pH to 6 with 1 mol / L sodium hydroxide solution. Add ammonium carbonate aqueous solution to the mixture. Adjust the pH to 11 with sodium hydroxide solution again. Seal and stir for 100 min. Let it stand to precipitate for 36 h to obtain precipitate A. Centrifuge to remove the supernatant. Add anhydrous ethanol or distilled water and ultrasonically clean for 3 min. After cleaning, centrifuge at 500 rpm to separate the cleaning solution from precipitate A. Change the cleaning solution for the next cleaning. Repeat the cleaning with each cleaning solution 3 times. Dry at 40℃ for 24 h. Ball mill at 100 kW 1000 rpm and sieve. The ground powder is sieved through 325 mesh and 625 mesh screens to obtain calcium carbonate template microspheres with an outer diameter of 25-45 micrometers and a smooth surface.
[0056] S2. Prepare a 0.06 mol / L diammonium hydrogen phosphate aqueous solution, add the calcium carbonate template microspheres obtained in S1, and add them until the ratio of calcium ions in calcium carbonate to phosphate ions in diammonium hydrogen phosphate is 5:3. Stir to form a suspension, adjust the pH of the suspension to 12 with 1 mol / L sodium hydroxide solution, and then transfer it to a reaction vessel with a polytetrafluoroethylene liner. Heat at 140℃ for 24 h, cool naturally to room temperature, pour out the internal suspension, centrifuge to remove the supernatant, add distilled water and ultrasonically clean for 3 min. After cleaning, centrifuge at 500 rpm to separate distilled water and precipitate B. Replace the distilled water for the next cleaning. Clean 3 times to obtain precipitate B, dry at 40℃ for 24 h, ball mill at 100 kW and 1000 rpm and sieve. The ground powder is then sieved through 325 mesh and 625 mesh sieves to obtain hydroxyapatite microspheres with an outer diameter of 25-45 micrometers and a smooth surface.
[0057] S3. Weigh 3.5 parts by weight, the intrinsic viscosity is 2.5m. 3 / kg of hyaluronic acid raw material and 31 parts of 1wt.% sodium hydroxide aqueous solution were added to a double planetary mixer container and stirred at 300rpm for 30min. Then, 1 part of ethylene glycol diacrylate sodium hydroxide aqueous solution (containing 0.25 parts of ethylene glycol diacrylate and 0.75 parts of 1wt.% sodium hydroxide aqueous solution) was added, followed by 10.5 parts of hydroxyapatite microspheres, to obtain the pre-crosslinking mixture. This mixture was then heated at 50℃ for 2.5h for crosslinking to obtain the post-crosslinking mixture. The post-crosslinking product was transferred to a pressure sieve and pulverized to a particle size of 100 micrometers. The refined post-crosslinking mixture was then... Add 90 parts of phosphate buffer and 10 parts of 1 mol / L hydrochloric acid to a shaker and shake at 75 rpm for 12 hours to obtain the predialysis mixture. Transfer the predialysis mixture to an automatic dispensing machine and set the dispensing pressure of the automatic dispensing machine to 1 MPa. Transfer the predialysis mixture to the dialysis bag through the automatic dispensing machine, with 8.5 g of predialysis mixture per centimeter of dialysis bag. Remove excess air from the dialysis bag and place it in a mixture of phosphate buffer and physiological saline in a stirrer for dialysis for 45 hours at a stirring speed of 300 rpm. Replace the phosphate buffer regularly during the period, for a total of 4 replacements. After dialysis, obtain the postdialysis mixture.
[0058] S4. The dialysis mixture obtained in S3 is placed in a dual planetary mixer container, and 6.7 parts of hydroxyapatite microspheres and 1 part of phosphate buffer are added. The mixture is stirred at 300 rpm for 30 min to ensure thorough dispersion. The cross-linked hyaluronic acid-smooth hydroxyapatite gel is then pulverized to 100 micrometers using a pressure sieve. After degassing, the cross-linked hyaluronic acid-smooth hydroxyapatite gel is transferred to a pre-filled syringe vacuum filling and capping machine. The filling capacity is set to 1 mL, and the working gas pressure is 1 MPa. The cross-linked hyaluronic acid-smooth hydroxyapatite gel is transferred to the pre-filled syringe using the vacuum filling and capping machine. The pre-filled syringe containing the cross-linked hyaluronic acid-smooth hydroxyapatite gel is then transferred to a 600-liter large-scale pressure steam sterilizer for sterilization. The sterilization temperature is set to 121°C, the sterilization time is 6 minutes, and the sterilization pressure is 0.6 MPa, thus obtaining the cross-linked hyaluronic acid-smooth hydroxyapatite gel.
[0059] Comparative Example 1
[0060] A method for preparing cross-linked hyaluronic acid-porous hydroxyapatite gel includes the following steps:
[0061] S1. Weigh 9.8 parts of Ca(NO3)2·4H2O and 0.2 parts of Zn(NO3)2·6H2O, dissolve them in 1000 mL of deionized water, and stir for 30 min to obtain the first solution; weigh 5.9 parts of (NH4)2HPO4 and 0.1 parts of Na2SeO3, dissolve them in deionized water, and stir for 30 min to obtain the second solution; slowly add the second solution to the first solution while stirring, and control the pH value between 10 and 11 with ammonia water to obtain the third solution; transfer the third solution to a reaction vessel and react at 120℃ for 12 h to obtain the fourth solution; filter the fourth solution, wash it with deionized water, repeat this process 3 times, and then freeze-dry it to obtain porous hydroxyapatite;
[0062] S2. Weigh 150g of the porous hydroxyapatite obtained in S1 and disperse it in 1L of deionized water containing 0.5% polyethylene glycol hydroxystearate. Stir well to obtain the fifth solution. Spray dry the fifth solution using a spray dryer at a spray temperature of 200℃, a feed rate of 5mL / min, an air volume of 300L / h, and a nozzle diameter of 1.0mm to obtain crude microspheres 1. Place the crude microspheres 1 into a muffle furnace for high-temperature calcination to obtain crude microspheres 2. Sift the crude microspheres 2 through a sieve to retain microspheres of 20-50μm, which are the desired porous hydroxyapatite microspheres.
[0063] S3. Weigh 3.5 parts by weight, the intrinsic viscosity is 2.5m. 3 / kg of hyaluronic acid raw material and 31 parts of 1wt.% sodium hydroxide aqueous solution were added to a double planetary mixer container and stirred at 300rpm for 30min. One part of butylene glycol diglycidyl ether sodium hydroxide aqueous solution (containing 0.25 parts of butylene glycol diglycidyl ether and 0.75 parts of 1wt.% sodium hydroxide aqueous solution) was added, followed by 8.9 parts of porous hydroxyapatite microspheres, to obtain the pre-crosslinking mixture. The mixture was heated at 50℃ for 2.5h for crosslinking to obtain the post-crosslinking mixture. The post-crosslinking product was transferred to a pressure sieve and pulverized to a particle size of 100 micrometers. Add 105 parts of phosphate buffer and 7.5 parts of 1 mol / L hydrochloric acid, place on a shaker and shake at 75 rpm for 12 hours to obtain the predialysis mixture. Transfer the predialysis mixture to an automatic dispensing machine, set the dispensing pressure of the automatic dispensing machine to 1 MPa, and transfer the predialysis mixture into the dialysis bag through the automatic dispensing machine. Each centimeter of the dialysis bag contains 8.5 grams of predialysis mixture. Remove excess air from the dialysis bag and place it in a mixture of phosphate buffer and physiological saline in a stirrer for dialysis for 45 hours at a stirring speed of 300 rpm. Replace the phosphate buffer regularly during the period, for a total of 4 replacements. After dialysis, the postdialysis mixture is obtained.
[0064] S4. The dialysis mixture obtained in S3 is placed in a dual planetary mixer container, and 4.7 parts of porous hydroxyapatite microspheres and 2 parts of phosphate buffer are added. The mixture is stirred at 300 rpm for 30 min to ensure thorough dispersion. The cross-linked hyaluronic acid-porous hydroxyapatite gel is then pulverized to 100 micrometers using a pressure sieve. After degassing, the cross-linked hyaluronic acid-porous hydroxyapatite gel is transferred to a pre-filled syringe vacuum filling and capping machine. The filling capacity is set to 1 mL, and the working gas pressure is 1 MPa. The cross-linked hyaluronic acid-porous hydroxyapatite gel is transferred to the pre-filled syringe using the vacuum filling and capping machine. The pre-filled syringe containing the cross-linked hyaluronic acid-porous hydroxyapatite gel is then transferred to a 600-liter large-scale pressure steam sterilizer for sterilization. The sterilization temperature is set to 121°C, the sterilization time is 6 minutes, and the sterilization pressure is 0.6 MPa, thus obtaining the cross-linked hyaluronic acid-porous hydroxyapatite gel.
[0065] Compared with Example 1, the main difference in this comparative example is that porous hydroxyapatite microspheres were prepared by spray drying, and smooth hydroxyapatite microspheres were replaced with porous hydroxyapatite microspheres.
[0066] Comparative Example 2
[0067] A method for preparing cross-linked hyaluronic acid gel includes the following steps:
[0068] S1 and S3. Weigh 3.5 parts by weight, the intrinsic viscosity is 2.5m. 3 / kg of hyaluronic acid raw material and 31 parts of 1wt.% sodium hydroxide aqueous solution were added to a double planetary mixer container and stirred at 300rpm for 30min. Then, 1 part of butylene glycol diglycidyl ether sodium hydroxide aqueous solution (containing 0.25 parts of butylene glycol diglycidyl ether and 0.75 parts of 1wt.% sodium hydroxide aqueous solution) was added to obtain the pre-crosslinking mixture. This mixture was then heated at 50℃ for 2.5h to obtain the post-crosslinking mixture. The post-crosslinking product was transferred to a pressure sieve and pulverized to a particle size of 100 micrometers. 105 parts of phosphorus were added to the refined post-crosslinking mixture. 7.5 parts of 1 mol / L hydrochloric acid were mixed with phosphate buffer and shaken on a shaker at 75 rpm for 12 hours to obtain a predialysis mixture. The predialysis mixture was then transferred to an automatic dispensing machine with a dispensing pressure of 1 MPa. The predialysis mixture was transferred into the dialysis bag through the automatic dispensing machine, with 8.5 g of predialysis mixture per centimeter of the dialysis bag. Excess air was removed from the dialysis bag, and the bag was placed in a mixture of phosphate buffer and physiological saline with a stirrer for dialysis for 45 hours at a stirring speed of 300 rpm. The phosphate buffer was changed periodically during the dialysis process, for a total of 4 changes. After dialysis, the postdialysis mixture was obtained.
[0069] S4. Place the dialysis mixture obtained in S3 into a dual planetary mixer container, add 2 parts phosphate buffer, and stir at 300 rpm for 30 min to fully disperse. Then, use a pressure sieve to pulverize the cross-linked hyaluronic acid gel to 100 micrometers. After degassing, transfer the cross-linked hyaluronic acid gel to a pre-filled syringe vacuum filling and capping machine. Set the filling volume to 1 mL and the working gas pressure to 1 MPa. Transfer the cross-linked hyaluronic acid gel to the pre-filled syringe using the vacuum filling and capping machine. Transfer the pre-filled syringe containing the cross-linked hyaluronic acid gel to a 600-liter large-scale pressure steam sterilizer for sterilization. Set the sterilization temperature to 121℃, the sterilization time to 6 minutes, and the sterilization pressure to 0.6 MPa to obtain the cross-linked hyaluronic acid gel.
[0070] Compared with Example 1, the main difference in this comparative example is that smooth hydroxyapatite microspheres are not added.
[0071] The performance of the samples prepared above was tested, and the specific test methods and results are shown below:
[0072] X-ray diffraction analysis of Example 1 and Comparative Example 1 of the present invention was performed using a polycrystalline powder X-ray diffractometer (Rigaku Ultima 4, Japan). The polycrystalline powder X-ray diffractometer was set to 40 kV and 40 mA with a copper target. The X-ray wavelength was 0.154056 nm, the scanning angle was 5 degrees to 90 degrees, and the scanning speed was 10 degrees per minute. Figure 1 , 2The images are scanning electron microscope images of the smooth hydroxyapatite microspheres prepared in Example 1 and the porous hydroxyapatite microspheres prepared in Comparative Example 1, respectively. Figure 1 The prepared smooth hydroxyapatite microspheres showed a particle size of 25-45 micrometers and a smooth surface. Figure 2 The prepared porous hydroxyapatite microspheres have a particle size of 25-45 micrometers and a rough surface with a porous interior.
[0073] The morphology of the smooth hydroxyapatite microspheres obtained in Example 1 of this invention was characterized using a scanning electron microscope (ZEISS, Sigma 300). The smooth hydroxyapatite microspheres were dispersed in ethanol, and the dispersed clear liquid was then dripped onto a dry and clean silicon wafer using a dropper and allowed to dry. After the solvent evaporated, the silicon wafer containing the sample was fixed on the sample stage surface and then transferred to a gold sputtering instrument for 15 seconds. Subsequently, it was transferred to the sample chamber of the scanning electron microscope, and after vacuuming, the surface morphology of the smooth hydroxyapatite microspheres was observed. Figure 3 The XRD pattern of the hydroxyapatite microspheres prepared in Example 1 is shown. After comparison with the standard card ICSD No. 89-4405, it is confirmed that the prepared substance is smooth hydroxyapatite.
[0074] Figure 4 The image shows a scanning electron microscope image of the cross-linked hyaluronic acid-smooth hydroxyapatite gel obtained in Example 1 of the present invention. As can be seen from the image, the cross-linked hyaluronic acid-smooth hydroxyapatite gel prepared by the present invention has a cross-linked network structure inside, and its cross-linked network embeds smooth hydroxyapatite microspheres.
[0075] The characterization test results of the other embodiments are basically consistent with those of Embodiment 1.
[0076] Human osteosarcoma cells (SaOS-2) were used for cell compatibility experiments. After stabilizing the human osteosarcoma cells in complete culture medium, each gel sample was tested at a concentration of 1.5 × 10⁻⁶. 5 Cells were seeded at a density of 1 cell in Example 1 and Comparative Examples 1 and 2. After culturing for 4 days, 400 μL MTS solution was added to each gel sample. After culturing at 37°C in the dark for half an hour, the absorbance at 490 nm was detected using an ELISA reader. This absorbance can characterize the cell survival rate on the gel sample. Figure 5 , Figure 6 The graphs show the absorbance bars for Example 1 and Comparative Examples 1 and 2 in the MTS cytotoxicity experiment. The absorbance is related to cell viability; the higher the absorbance, the higher the cell viability. As shown in the graphs, the cell viability of Example 1 is about 1.5 times that of Comparative Example 1 and about twice that of Comparative Example 2. This indicates that the addition of hydroxyapatite microspheres can stimulate the proliferation of human osteosarcoma cells SaOS-2, and the effect of adding smooth hydroxyapatite microspheres is better than that of adding porous hydroxyapatite microspheres.
[0077] Two hundred microliters of gel from Comparative Example 1 and Example 1 were subcutaneously injected into five-week-old female nude mice (Comparative Example 2 could not be tested because its volume rapidly decreased to less than 50% one week after subcutaneous injection). At weeks 0, 4, and 12, both groups underwent MRI image volume analysis (Agilent 9.4T / 160AS; Agilent Technologies, Santa Clara, CA, USA) under 1.5% isoflurane and 1.0 L / min oxygen conditions, obtaining T2-weighted axial images. The slice thickness of the axial images was 0.3 mm. Gel locations were identified and marked within the obtained images, and gel stability was characterized based on the size of the marked area. Figure 7 The T2-weighted axial images of Comparative Example 1 and Example 1 show that, over time after injection, the filling volume of the cross-linked hyaluronic acid-porous hydroxyapatite gel in Comparative Example 1 rapidly decreased, falling below 50% after 24 weeks. In contrast, the filling volume of the cross-linked hyaluronic acid-smooth hydroxyapatite gel in Example 1 slightly decreased, reaching over 70% of its original volume after 24 weeks. This indicates that the cross-linked hyaluronic acid-smooth hydroxyapatite gel prepared in Example 1 exhibits better in vivo stability and a longer-lasting filling effect than the cross-linked hyaluronic acid-porous hydroxyapatite gel in Comparative Example 1.
[0078] Twelve weeks after gel injection, biopsy specimens were taken from the injection site and fixed in 10% formaldehyde solution for 24 hours. The specimens were then embedded in paraffin, sectioned, stained with hematoxylin and eosin, and observed. Figure 8 The images show stained tissue sections. As can be seen from the figures, the dermal layer of the nude mouse tissue sections prepared after injection of cross-linked hyaluronic acid-smooth hydroxyapatite gel in Example 1 is thicker than that of cross-linked hyaluronic acid-porous hydroxyapatite gel in Comparative Example 1. This indicates that the addition of smooth hydroxyapatite microspheres can better stimulate the growth of dermal tissue and provide better filling effect for the skin.
[0079] In summary, the present invention utilizes a hydrothermal method to prepare dense, smooth hydroxyapatite microspheres. The smooth surface helps reduce the injection extrusion force of the cross-linked hyaluronic acid-smooth hydroxyapatite gel, and the dense structure results in a higher microsphere content, which is beneficial for stimulating the growth of dermal tissue. This makes the cross-linked hyaluronic acid-smooth hydroxyapatite gel of the present invention less prone to degradation in the human body fluid environment, with a long filling duration and sustained support for the growth of human filler tissue, thus providing excellent filling effect to the skin for a long time.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a cross-linked hyaluronic acid-smooth hydroxyapatite gel, characterized in that, Includes the following steps: S1. Prepare solutions A and B with concentrations of 0.1–5 mol / L. Add a morphology control agent to solution B, stir and mix, adjust the pH to 5–8, and then add solution A to the mixed solution B. Adjust the pH of the mixture to 9–14, seal and stir, let it stand to precipitate, and obtain precipitate A. Centrifuge precipitate A, ultrasonically clean it, dry it, ball mill it and sieve it to obtain calcium carbonate template microspheres. Solution A is one or more of sodium carbonate aqueous solution, potassium carbonate aqueous solution, and ammonium carbonate aqueous solution; solution B is one or more of calcium chloride aqueous solution, calcium hydroxide aqueous solution, and calcium nitrate aqueous solution. S2. Prepare 0.01-1 mol / L solution C, add calcium carbonate template microspheres obtained in S1, stir to form a suspension, adjust the pH of the suspension to 8-14, heat, cool naturally to room temperature, centrifuge, ultrasonically clean to obtain precipitate B, dry precipitate B, ball mill and sieve to obtain hydroxyapatite microspheres. The C solution is one or more of the following: diammonium hydrogen phosphate aqueous solution, disodium hydrogen phosphate aqueous solution, and dipotassium hydrogen phosphate aqueous solution; S3. Weigh out the hyaluronic acid raw material and alkaline solution according to the mass fraction, stir, add the hyaluronic acid crosslinking agent alkaline solution, add the hydroxyapatite microspheres obtained in S2, and obtain the pre-crosslinking mixture. Heat and crosslink to obtain the post-crosslinking mixture, sieve under pressure to refine, add phosphate buffer and acid neutralization solution to the refined post-crosslinking mixture, shake and mix to obtain the pre-dialysis mixture, transfer the pre-dialysis mixture to the dialysis bag, place it in the dialysis solution for dialysis, and obtain the post-dialysis mixture. S4. Add the hydroxyapatite microspheres and phosphate buffer obtained in S2 to the dialysis mixture obtained in S3, stir to disperse fully, refine, vacuum fill, and steam sterilize to obtain the cross-linked hyaluronic acid-smooth hydroxyapatite gel. The morphology control agent mentioned in S1 is citric acid; its concentration in solution B is 0.1–0.5 mol / L. The sealing and stirring time mentioned in S1 is 10 to 120 minutes; the drying temperature mentioned in S1 is 40 to 100°C. The heating temperature described in S2 is 100–160°C, and the time is 6–36 hours; The drying temperature described in S2 is 40-80℃, and the drying time is 1-24 hours; The hydroxyapatite microspheres described in S3 have a mass fraction of 2.5 to 25 parts; The amount of hydroxyapatite microspheres added in S4 is 1.5 to 15 parts, and the amount of phosphate buffer added is 0.2 to 2 parts.
2. The method for preparing cross-linked hyaluronic acid-smooth hydroxyapatite gel as described in claim 1, characterized in that: The stirring and mixing agitators described in S1 to S4 have independently power ratings of 1 to 10 kW and independently rotation speed ratings of 300 to 3000 rpm. The ultrasonic cleaning time in S1 and S2 is 1 to 10 minutes, and the number of times is 1 to 10. The ultrasonic cleaning also includes a centrifugation step after cleaning, and the centrifugation speed is 100 to 3000 rpm. The ball mill sieving machines described in S1 and S2 have an independent power of 5 to 400 kilowatts and an independent speed of 500 to 2000 rpm. The sieving uses 325 mesh and 625 mesh screens respectively.
3. The method for preparing cross-linked hyaluronic acid-smooth hydroxyapatite gel as described in claim 1, characterized in that: The settling time in S1 is 0 to 72 hours; the ultrasonic cleaning solution is anhydrous ethanol and / or distilled water, and each cleaning solution is used at least once.
4. The method for preparing cross-linked hyaluronic acid-smooth hydroxyapatite gel as described in claim 1, characterized in that: The ratio of the amount of calcium ions in the calcium carbonate template microspheres described in S2 to the amount of phosphate ions in solution C should be 5:3; the ultrasonic cleaning solution is distilled water.
5. The method for preparing cross-linked hyaluronic acid-smooth hydroxyapatite gel as described in claim 1, characterized in that: The intrinsic viscosity of the hyaluronic acid raw material described in S3 is 0.5–4 m. 3 / kg, in parts by weight of 1 to 10; the alkaline solution is an alkaline aqueous solution of sodium hydroxide and / or potassium hydroxide, in parts by weight of 10 to 100, with a concentration of 0.1 to 10 wt.%; The hyaluronic acid crosslinking agent in the alkaline solution is one or more of butylene glycol diglycidyl ether, genipin, ethylene glycol diacrylate, adipate dihydrazide, and divinyl sulfone. The mass fraction of the hyaluronic acid crosslinking agent is 0.06 to 0.6 parts, and the mass fraction of the alkaline solution is 0.2 to 2 parts.
6. The method for preparing cross-linked hyaluronic acid-smooth hydroxyapatite gel as described in claim 1, characterized in that: The heating crosslinking temperature described in S3 is 30–70°C, and the time is 0.5–5 hours.
7. The method for preparing cross-linked hyaluronic acid-smooth hydroxyapatite gel as described in claim 1, characterized in that: The phosphate buffer solution in S3 has a mass fraction of 30–300 parts; the acidic neutralizing solution is hydrochloric acid and / or sulfuric acid, with a concentration of 0.1–5 mol / L and a mass fraction of 2–20 parts; the shaking mixing speed is 50–100 rpm, and the time is 1–48 hours; the dialysate is phosphate buffer and / or physiological saline; the dialysis stirring rate is 100–1000 rpm, the time is 10–72 hours, and the number of times the solution is changed is 1–10.
8. The method for preparing cross-linked hyaluronic acid-smooth hydroxyapatite gel as described in claim 1, characterized in that: The particle size after refinement in S4 is 60–1500 micrometers; the steam sterilization pressure is 0.6 MPa, the temperature is 100–150°C, and the time is 1–20 min.
9. A cross-linked hyaluronic acid-smooth hydroxyapatite gel, characterized in that, It is prepared according to any one of the preparation methods in claims 1 to 8.
Citation Information
Patent Citations
Preparation method of injection type facial filling hydrogel for cosmetic and plastic surgery
CN114767934A
Injectable gels comprising cross-linked hyaluronic acid and hydroxyapatite, and methods of manufacturing thereof
CN109906073A